2013
DOI: 10.1016/j.pcd.2012.10.046
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in patients with type 2 diabetes mellitus in Iran: a national survey

Abstract: Introduction: The aim of this study was to measure health-related quality of life (HRQoL) in Iranian people with Type 2 Diabetes Mellitus using two different measures and examines which socio-demographic and diabetes-related characteristics are associated with better quality of life based on a nationally distributed sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
44
1
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(76 citation statements)
references
References 25 publications
26
44
1
5
Order By: Relevance
“…A higher education level was associated with better QoL. This result is consistent with data obtained in a previous Iranian study [51]. A study in the United Arab Emirates, which used another score for QoL measurement, matches our result [53].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A higher education level was associated with better QoL. This result is consistent with data obtained in a previous Iranian study [51]. A study in the United Arab Emirates, which used another score for QoL measurement, matches our result [53].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we found a significant association between higher QoL and younger age. This finding is in agreement with that obtained by an Iranian study [51]. This contrasts with the study of O'Reilly et al, which explained that HRQoL gets better when the patient is older in age [52].…”
Section: Discussionsupporting
confidence: 90%
“…Instead, the EQ-5D score was slightly lower (0.87) in OHA group compared to the other group (0.89) (p=0.17, ns). These findings are in agreement with the previous literature [21,22,36,37] that reported no significant association between HRQoL and treatment type using EQ-5D scores. Among the other substantial differences that were non-significant, patients with healthy weights reported a lower VAS scores than the pre-obese or obese patients; a higher VAS mean value was recorded in the non-adherent patients than the medium or adherent patients.…”
Section: Butt Et Alsupporting
confidence: 93%
“…21 While the HRQOL of diabetic patients in Iran is one of the most important outcome measures, there are limited studies that evaluated the quality of people with diabetes in southwest of Iran. 22,23 In order to fill the gap in this area, this study was carried out to assess the QOL among type 2 diabetes patients in southwest of Iran and to determine which socio-demographic and clinical characteristics are related with better QOL.…”
Section: Introductionmentioning
confidence: 99%